Trend in Gastric Outlet Obstruction at Patients Attending Tribhuvan University Teaching Hospital, Kathmandu, Nepal - Thakur, Deepak Kumar; Ghimire, B; Singh, YP (Birat Journal of Health Sciences, 2017)
Introduction Gastric outlet obstruction (GOO) involves obstruc_on in the antro-pyloric region or bulb of duodenum. Malignancy is common cause of GOO in adults but many patients with GOO have benign causes. Despite the improvement in medical management, about 5% patients with complicated duodenal ulcer disease and 1%-2% with complicated gastric ulcer disease respectively develop this problem. Objective The purpose of this study was to find the etiologies of GOO, their management options and outcome in Tribhuvan University Teaching Hospital. Methodology In this retrospective study, the records of 44 patients admited with diagnosis of GOO from September 2007 to August 2010 in the Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal were retrieved. Patients’ demography, etiologies of GOO, treatment given and their outcome were analysed. Results Thirty two patients (73%) were male and 12 (27%) were female with M:F ratio of 2.7:1. The mean age of patients was 57.40 years and duration of symptoms 2.68 months. Carcinoma of stomach, 28 cases (64%) was most common ecology of GOO followed by PUD, 9 (21%), duodenal malignancy,3 (7%), corrosive stricture, 2 (5%), advanced gallbladder carcinoma, 1 (2%) and chronic pancreatis, 1 (2%). Seventeen (39%) patients were treated by gastrojejunostomy, 14 (32%) by subtotal gastrectomy and gastrojejunostomy, 5 (11%) by truncal vagotomy and gastrojejunostomy, 4 (9%) by medical management, 2 (4.5%) by feeding jejunostomy, and 2 (4.5%) were discharged on request. Complications occurred in 7 (16%) patients and mortality in 1 (2%). Twenty three (52%) patients were candidates for chemotherapy either in an adjuvant or palliative seting. Conclusion Gastric malignancy was the most common cause of gastric outlet obstruction. Most of the patients in our setup presented with advanced disease and were candidates of palliative treatment only. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 219-221